Analysis of Factors Affecting Pais Optimization in Performance Assessment Police Personnel (Human Resources Bureau of Riau Police) - Dimas Huda Luthfiyani; Abshor Marantika; Kasmawati; Mhd Fitra Pratama (LP2M IAIN Palopo, 2025)
This study uses a quantitative method with a descriptive and verifiable research design. The population in this study is all personnel in the Riau Police Human Resources Bureau involved in the use of the Performance Appraisal Information System (PAIS), totaling 77 people. Samples were taken using census sampling techniques, as the population is relatively small. Thus, all members of the population are used as research samples. Based on the results of the study on the analysis of factors that affect the optimization of PAIS in the assessment of the performance of police personnel at the Riau Police Human Resources Bureau, it is concluded that human resources, information system technology, and policies and regulations have a significant influence both partially and simultaneously on the optimization of PAIS. These three factors together contributed 57.8% to the optimization of PAIS, while the remaining 42.2% were influenced by other factors outside the variables studied. These findings affirm the importance of improving the quality of human resources, developing information technology, and developing appropriate policies to maximize the performance of the assessment system.